Perbandingan Prediksi Kebangkrutan Menggunakan Metode Grover, Metode Altman Z-Score dan Metode Springate - Nur Gita Suryati Putri; Victoria Ari Palma Akadiati; Imelda Sinaga (Komunitas Dosen Indonesia, 2023)
This study aims to analyze the bankruptcy rate of companies using the Grover model, Altman Z-score model, and Springate model. This type of quantitative research with the population uses companies that conducted IPOs in 2021. The sampling technique used is purposive sampling and the number of samples obtained based on predetermined criteria is 54 company samples. The results of this study showed that sample companies that predicted bankruptcy using the Grover method had an accuracy rate of 83%, and an error rate of 17%. The Altman Z-score method has an accuracy rate of 87%, an error rate of 9%, and a gray area rate of 4%. The Springate method has the highest accuracy rate of 94%, and an error rate of 6%. This bankruptcy prediction analysis can help company owners to immediately anticipate the factors that cause bankruptcy and for investors can be used as information in making decisions to invest in shares in IPO companies in 2021.